2002
DOI: 10.1038/nbt0402-396
|View full text |Cite
|
Sign up to set email alerts
|

Expression of exogenous protein in the egg white of transgenic chickens

Abstract: Using a replication-deficient retroviral vector based on the avian leukosis virus (ALV), we inserted into the chicken genome a transgene encoding a secreted protein, beta-lactamase, under the control of the ubiquitous cytomegalovirus (CMV) promoter. Biologically active beta-lactamase was secreted into the serum and egg white of four generations of transgenic chickens. The expression levels were similar in successive generations, and expression levels in the magnum of the oviduct were constant over at least 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
2
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 16 publications
0
73
2
7
Order By: Relevance
“…defective avian leukosis virus was used to generate hens expressing the reporter ␤-lactamase from a ubiquitous promoter. While ␤-lactamase was detected in egg white of transgenic hens, the quantity of protein, efficiency of transgenesis, and germ-line transmission rate were all low (17,18). Arian leukosis virus was also used to generate chickens expressing human IFN-␣-2b at higher levels than had been reported for ␤-lactamase (3), but the efficiency with which transgenic birds were generated remained very low (a single G 1 cockerel from 1,597 chicks hatched), presumably a consequence of the low-titer vector used.…”
Section: Discussionmentioning
confidence: 99%
“…defective avian leukosis virus was used to generate hens expressing the reporter ␤-lactamase from a ubiquitous promoter. While ␤-lactamase was detected in egg white of transgenic hens, the quantity of protein, efficiency of transgenesis, and germ-line transmission rate were all low (17,18). Arian leukosis virus was also used to generate chickens expressing human IFN-␣-2b at higher levels than had been reported for ␤-lactamase (3), but the efficiency with which transgenic birds were generated remained very low (a single G 1 cockerel from 1,597 chicks hatched), presumably a consequence of the low-titer vector used.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic birds generated by using oncoretroviral vectors have been shown to express low levels of transgene in the egg whites of laid eggs (32). The chicken ovalbumin promoter has been suggested as a regulatory sequence for directing protein expression in egg whites (33).…”
Section: Discussionmentioning
confidence: 99%
“…Since Salter et al (1987) first demonstrated the production of transgenic chickens by injecting avian leukosis viruses into blastoderm, many types of virus such as retrovirus and lentivirus were attempted to generate the transgenic birds. Using a replication-deficient retroviral vector based on the avian leukosis virus (ALV), Harvey et al (2002) reported that the biofunational β-lactamase was secreted and deposited into egg white of four generations of transgenic chickens which were transferred the transgene controlled by the ubiquitous cytomegalovirus (CMV) promoter.…”
Section: Introductionmentioning
confidence: 99%